Comparative Study on the Effectiveness of Official Media Coverage and Self-Media Communication of a Friction Event in Tangshan, China Based on Framing Theory - Zhu, Yushu; Hu, Jiaxin (Journal of Humanities and Social Sciences Studies, 2023)
On June 10, 2022, an attack at a barbeque restaurant in Tangshan, China, triggered considerable public concern on the Internet and drew the utmost attention from departments responsible for relevant matters. The case advanced swiftly and yielded the best possible outcomes with the collaboration of numerous parties. The 2022 restaurant attack in Tangshan is a successful illustration of how the interaction between new mainstream media and self-media supervision of public opinion can contribute to the resolution of social issues. It can provide references for the efficient resolution of future social issues. Based on the framing theory, this research studies the highly-searched posts by netizens and People’s Daily’s official posts on Weibo through comparison and content analysis. After analyzing the reporting rules, focuses, and impacts of both official and self-media, it is concluded that the new mainstream media and self-media public opinion supervision each have their own benefits and drawbacks. The two complement one another in revealing social issues, thereby boosting cooperation between the government and the people, which is helpful for enhancing the effectiveness of the departments responsible for related matters and supporting the harmonious development of society.